Newt Gingrich the rise and fall of a party entrepreneur - Green, Matthew N., 1970-; Crouch, Jeffrey (Congressional leaders, 2022)
"From the moment he entered politics, Newt Gingrich was laser-focused on one goal: to regain control of the House of Representatives and, as a result, to facilitate a conservative shift in American society. To achieve this goal he overturned long-held Congressional norms. In a June 1978 speech, he said that what the Republicans needed was not "another generation of cautious, prudent, careful, bland, irrelevant, quasi-leaders" but individuals "willing to take risks, willing to stand up in a slug fest and match it out with their opponent." That was precisely what Gingrich did, beginning with his election in 1978. He finally achieved his goal with the 1994 midterm elections, propelled by his Contract with America, that ended forty years of Democratic control of the House. But only five years later Gingrich found himself forced to resign, abruptly ending his tenure in politics after twenty years. As a polarizing and consequential figure, Gingrich has been the subject of extensive discussion, but the efforts to make sense of his time in office have resulted in conflicting accounts. Political scientists Matthew Green and Jeffrey Crouch have mined the archives and argue in their contribution to the Congressional Leaders series that Gingrich is best understood as a party entrepreneur. Congressional entrepreneurs tend to be either procedural entrepreneurs, who bring about institutional reform and rule changes, or legislative entrepreneurs, who introduce bills and guide them to enactment. Gingrich was a third type: a party entrepreneur-someone who works to achieve their party's collective goals. This perspective helps to make sense of someone who was creative and successful in gaining power but not effective in using and sustaining it. Newt Gingrich is a comprehensive look at Gingrich's time in Congress and offers a new perspective on one of the most significant and controversial American politicians"--